Prediction of disease severity in patients with febrile illnesses in resource-limited settings - Chandna, A (2023)
Febrile illnesses present unique challenges for health systems with scarce resources. Large volumes of mostly self-limiting diseases accompanied by high case-fatality rates for the small proportion of serious infections mean that risk stratification tools must have high sensitivities and/or specificities according to their proposed contexts of use. Unfortunately, accuracy and reliability of existing tools are sub-optimal and they are often impractical for deployment in resource-limited settings.